ChemInform Abstract: A Novel One‐Pot Sulfonyloxylactonization of Alkenoic Acids Mediated by Hypervalent Iodine Species Generated in situ from Ammonium Iodide. Issue 20 (20th May 2014) - Hu, Jiantao; Zhu, Min; Xu, Yuan; Yan, Jie
Abstract Scope and limitations of the novel method are established.